Solution concepts in multi-objective location problems with variable domination structure - Zargini, Bettina (European Journal of Applied Sciences, 2021)
We study multi-objective location problems with respect to a variable domination structure. To solve such problems, we apply minimal and nondominated solutions from vector optimization problems with respect to a variable domination structure. We investigate these solution concepts to be used in multi-objective location problems. These solution concepts are proposed for multi-objective location problems where variable preferences of objective functions at each location are assumed; our results are applied for selecting a location to establish a new branch.